2018
DOI: 10.7567/jjap.57.122301
|View full text |Cite
|
Sign up to set email alerts
|

Rapid progression and subsequent saturation of polarization-type potential-induced degradation of n-type front-emitter crystalline-silicon photovoltaic modules

Abstract: In this study, we investigated progression of potential-induced degradation (PID) in photovoltaic modules fabricated from n-type-based crystalline-silicon cells with front p+ emitters. In PID tests in which a bias of −1000 V was applied to the modules, they started to degrade within 5 s and their degradation saturated within 60 s. This behavior suggested that the PID was caused by positive charge accumulation in the front passivation films. Performing PID tests with a bias of −1500 V revealed that the degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
126
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(136 citation statements)
references
References 38 publications
9
126
1
Order By: Relevance
“…These K centers can be neutral K 0 , positively charged K + and negatively charged K − depending on the number of electrons on the dangling bond 30 . When the cell is negatively biased, electrons are extracted from K 0 and K − centers, leaving only K + centers 29 . One study actually showed that solar modules based on cells without SiN x did not experience PID‐p, 20 possibly due to the absence of K + centers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These K centers can be neutral K 0 , positively charged K + and negatively charged K − depending on the number of electrons on the dangling bond 30 . When the cell is negatively biased, electrons are extracted from K 0 and K − centers, leaving only K + centers 29 . One study actually showed that solar modules based on cells without SiN x did not experience PID‐p, 20 possibly due to the absence of K + centers.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, studies have shown that solar modules with Na-free substrate still suffered from PID-p. 26,27 One possible source of positive charges proposed by Yamaguchi et al is K centers in SiN x film itself, which are dangling bonds of Si atoms backbonded to three N atoms. 28,29 These K centers can be neutral K 0 , positively charged K + and negatively charged K − depending on the number of electrons on the dangling bond. 30 When the cell is negatively biased, electrons are extracted from K 0 and K − centers, leaving only K + centers.…”
Section: Effect Of Sio X Layer On Pid Of P-type Bifacial Monocrystamentioning
confidence: 99%
See 1 more Smart Citation
“…For n‐type PERT solar cells, Yamaguchi et al have proposed that PID‐p is caused by a change of K center charge state in the silicon nitride layer. [ 14 ] These results are supported by capacitance–voltage ( C – V ) and electron‐spin‐resonance (ESR) that revealed density of K‐centers and their charge state. In case of p‐type PERC+, Luo et al have discussed that positively charged sodium ions accumulate in the silicon nitride layer and compensate the negatives charges of the aluminum oxide layer, leading to failure of the field effect passivation.…”
Section: Introductionmentioning
confidence: 84%
“…14,15,[24][25][26][27][28][29] The PID-p in n-type IBC solar cells occurs under positive potential conditions, 9,[30][31][32] whereas the PID-p in n-type solar cells with a front p + emitter is observed under negative potential conditions. 14,15,[24][25][26][27][28][29] Both can be explained by the surface recombination of minority carriers arising from the charge fixed on the silicon dangling bonds back-bonded with nitrogen, known as "K centers," in the SiN x ARC layer. 9,24,25 If the ARC of p-type c-Si solar cells is constructed by the SiN x stacked on SiO 2 layers, PID-p can occur even in the p-type c-Si solar cells by applying a high positive voltage.…”
Section: Introductionmentioning
confidence: 99%